What Technology Skills Do Developers Need? A Text Analysis of Job Listings in Library and Information Science (LIS) from Jobs.code4lib.org - Maceli, Monica (Information Technology and Libraries, 2015)
Technology plays an indisputably vital role in library and information science (LIS) work; this rapidly moving landscape can create challenges for practitioners and educators seeking to keep pace with such change. In pursuit of building our understanding of currently sought technology competencies in developer-oriented positions within LIS, this paper reports the results of a text analysis of a large collection of job listings culled from the Code4lib jobs website. Beginning over a decade ago as a popular mailing list covering the intersection of technology and library work, the Code4lib organization's current offerings include a website that collects and organizes LIS-related technology job listings. The results of the text analysis of this dataset suggest the currently vital technology skills and concepts that existing and aspiring practitioners may target in their continuing education as developers.